Translation as Adaptation: An Exploration of Howell and Caroe’s English - Nasir Mehmood , Hazrat Umar (JSSH, 2023)
The article is an attempt to explore translation as adaptation. It examines adaptation as one of the strategies in literary translation by investigating how poetry translation presents a challenge in terms of transfer of content and form of a poem. The source text (ST) consists of two Pashto poems of Khushhal Khan Khattak, rendered in English by Caroe and Howell. The study is significant as translation of poetry can help in introducing a poet in the international mainstream of literature. As the nature of the study demands, research method is qualitative in nature as it is based on interpretive tradition underpinned by Nida’s model.